MODAL PSIKOLOGIS DAN KEPRIBADIAN PROAKTIF TERHADAP PERILAKU KERJA INOVATIF PADA KARYAWAN - Dewi, Dinda Puspita; Prestiana, Novita Dian Iva; Setiawan, Rony (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2024)
This study aims to determine the relationship between psychological capital and innovative work behavior and proactive personality with innovative work behavior, as well as the influence of psychological capital and proactive personality on innovative work behavior. This research is a research with non-experimental quantitative methods. The subjects of this study were 51 employees from PT. Cahaya Citra Indah is a company engaged in the property sector. This research uses population studies because the total population is below 100. The data collection method in this study uses interviews and a psychological measurement scale. The research instrument used was a psychologicalcapital scale with an Alpha Cornbach reliability value of 0.937, a proactive personalityscale with an Alpha Cornbach reliability value of 0.934, and an innovative work behavior scale withan Alpha Cornbach reliability value of 0.887. The data analysis technique uses the Rank Spearman correlation test and the Multiple Linear Regression test. This study found that psychological capital with innovative work behavior has a positive relationship that is equal to 0.887 and, proactive personality with innovative work behavior has a positive relationship that is equal to 0.852. Then there is the influence of psychological capital and proactive personality on innovative work behaviorwith an R squared value of 0.841 or 84.1%